2019
DOI: 10.31234/osf.io/bfxmd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental rotation of feet in individuals with Body Integrity Identity Disorder, lower-limb amputees, and normally-limbed controls

Abstract: Body Integrity Identity Disorder (BIID) is a non-psychotic condition wherein individuals desire amputation or paralysis of one or more healthy, fully-functioning limbs (predominantly the legs). Individuals with BIID have been suggested to have a mismatch between the perceived mental representation of the body and its actual physical structure, such that their desired identity matches that of a lower-limb amputee. Accordingly, studies have reported an altered central network involving body representation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Similar to previous studies investigating left–right discrimination of feet (Coslett et al, 2010a; Curtze et al, 2010; Stone et al, 2019), task accuracy was high (proportion of correct responses: 0.94, see Table 3 for overall means and Table for model results).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Similar to previous studies investigating left–right discrimination of feet (Coslett et al, 2010a; Curtze et al, 2010; Stone et al, 2019), task accuracy was high (proportion of correct responses: 0.94, see Table 3 for overall means and Table for model results).…”
Section: Resultssupporting
confidence: 84%
“…Findings augment conflicting evidence of body schema impairments post‐LLL. For example our findings support those of Palermo et al (2018), where 14 male participants with LLL were less accurate than 11 controls during a left–right discrimination task, but contrast those of Stone et al (2019) and Curtze et al (2010) who found no differences in left–right discrimination among adults with LLL ( n = 19 and n = 18 respectively) when compared to controls ( n = 33 and n = 18 respectively). While we found significant differences between our moderately sized sample of controls ( n = 37) and adults with LLL ( n = 68), the left–right discrimination task may not be sensitive enough to detect body schema impairments among smaller, heterogeneous samples post‐LLL.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations